SUSTAINABILITY ANALYSIS OF FEASIBILITY OF ANIMAL CUTTING HOUSES, CITY OF JAMBI (CASE STUDY: TECHNICAL AND ENVIRONMENTAL STUDY) - fianti fauzan; Hutwan Syarifuddin; Syafril Hadi (Universitas Jambi, 2021)
The need for meat consumption as a protein source is increasing along with the increasing awareness and population in Indonesia. Jambi City is one of the most populous areas in Jambi Province and has a high demand for meat consumption. Slaughterhouse (RPH) is one of the efforts of the Regional Government to meet the needs of meat in the city. This study discusses the feasibility of RPH Jambi City. The method used in this research is the interpretative structural modelling (ISM) method; the results of the study inform that the feasibility of slaughterhouses in Jambi City from the technical and environmental aspects is good enough. The RPH of Jambi City has fulfilled the important requirements for the establishment of slaughterhouses, such as the availability of clean water, cutting tools, cleanliness, electricity, staff, veterinarians, and administrative matters the waste produced by the RPH is still above environmental quality so that processing is required. The ISM method analysis result shows that all elements are in quadrant 3, namely linkage. Linkage is a quadrant that shows equally strong between variable driver power (DP) and dependence (D). That is, variable DP and variable D must be both increased, without any more important priorities to be resolved. Key words: RPH feasibility, ISM method, Jambi City RPH, ISM elements